The Three-Species Consortium of Genetically Improved Strains Cupriavidus necator RW112, Burkholderia xenovorans RW118, and Pseudomonas pseudoalcaligenes RW120 Grows with Technical Polychlorobiphenyl, Aroclor 1242 - Wittich, Regina-Michaela; Lang, Elke; Hernández-Sánchez, Verónica (Frontiers in Microbiology, 2013)
Burkholderia xenovorans LB400, Cupriavidus necator H850, and Pseudomonas pseudoalcaligenes KF707 are bacterial strains able to mineralize biphenyl and to co-oxidize many of its halogenated derivatives (PCBs). Only strain LB400 also mineralizes a few mono- and dichlorobiphenyls, due to the presence of a functioning chlorocatechol pathway. Here, we used a Tn5-based minitransposon shuttle system to chromosomically introduce genes tcbRCDEF, encoding the chlorocatechol pathway into KF707, and genes cbdABC encoding a 2-chlorobenzoate 1,2-dioxygenase into KF707 and LB400, as well as transposon Tn4653 from the TOL plasmid providing genes xylXYZL, encoding a broad-range toluate (methylbenzoate) dioxygenase and its dihydrodiol dehydrogenase, to extend the range for the mineralization of halogenated benzoates in LB400 and in KF707. The engineered derivatives of LB400, and KF707 thus gained the ability for the mineralization of all isomeric monochloro- and bromobenzoates of the so-called lower pathway which, consequently, also allowed the mineralization of all monochlorobiphenyls and a number of di- and trichlorobiphenyls, thus preventing the accumulation of halobenzoates and of catabolites thereof. LB400 and KF707 also grow with the two commercial PCB formulations, Aroclor 1221 and Aroclor 1232, as the sole carbon and energy sources, but not with higher halogenated PCB mixtures, similar to the already published strain RW112. Repeated exposition of the modified LB400 to short pulses of UV light, over a prolonged period of time, allowed the isolation of a derivative of LB400, termed RW118, capable of growth with Aroclor 1016 still containing only traces of biphenyl, and in co-culture with modified KF707 termed RW120, and modified H850 (RW112) with Aroclor 1242, the commercial mixture already void of biphenyl and monochlorobiphenyls.